1991
DOI: 10.1021/bi00235a019
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution NMR studies of chimeric DNA-RNA-DNA duplexes, heteronomous base pairing, and continuous base stacking at junctions

Abstract: Two symmetrical DNA-RNA-DNA duplex chimeras, d(CGCG)r(AAUU)d(CGCG) (designated rAAUU) and d(CGCG)r(UAUA)d(CGCG) (designated rUAUA), and a nonsymmetrical chimeric duplex, d(CGTT)r(AUAA)d(TGCG)/d(CGCA)r(UUAU)d(A ACG) (designated rAUAA), as well as their pure DNA analogues, containing dU instead of T, have been synthesized by solid-phase phosphoramidite methods and studied by high-resolution NMR techniques. The 1D imino proton NOE spectra of these d-r-d chimeras indicate normal Watson-Crick hydrogen bonding and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…Earlier NMR investigations with a dGn rC11-dC16 Okazaki-type hybrid had suggested a coexistence of two helical conformations in the fragment (22) and models of A-B junctions comprising 3 base pairs were proposed (23). More recently, NMR studies on short [DNA-RNA-DNA]2 duplex chimeras showed a structural perturbation at the junction site that is spread over at least 2 base pairs (24). Such junctions occurring over a few base pairs would provide evidence against the propagation of secondary structure along the DNA duplex.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier NMR investigations with a dGn rC11-dC16 Okazaki-type hybrid had suggested a coexistence of two helical conformations in the fragment (22) and models of A-B junctions comprising 3 base pairs were proposed (23). More recently, NMR studies on short [DNA-RNA-DNA]2 duplex chimeras showed a structural perturbation at the junction site that is spread over at least 2 base pairs (24). Such junctions occurring over a few base pairs would provide evidence against the propagation of secondary structure along the DNA duplex.…”
Section: Resultsmentioning
confidence: 99%
“…Recent NMR data suggest that the deoxyribose residues in DNA/RNA hybrid duplexes remain in a conformation that is similar to the 2'-endo conformation rather than converting to the 3/-endo conformation (Chou et al, 1989;Katahira et al, 1990), and the helical repeat is different for DNA/RNA duplexes than for RNA/RNA duplexes [Bhattacharyya et al, 1990; see also Gast and Hagerman (1991)l. Thus, some or all of the deoxyribose residues might need to alter their sugar conformation in order to allow the P1 duplex to dock correctly into its tertiary interactions and/or to align the reactive phosphoryl group in the active site.…”
Section: Separation Of the Effect Of Each 2'-hydroxyl Into Effects Onmentioning
confidence: 99%
“…This simple model is consistent with the limited data that suggest that oligonucleotides with 2'-substituents that favor the 3'-endo conformation tend for form stronger duplexes with RNA [see references in text and Janik et al (1972) and Guschlbauer and Jankowski (1980)l. However, deoxyribose residues in at least some RNA/DNA hybrid duplexes are not converted to 3'-endo (Chou et al, 1989;Katahira et al, 1990). According to the simple model, these hybrid duplexes would avoid the destabilization from conversion of the sugar conformation by adopting an alternative helix geometry.…”
Section: Separation Of the Effect Of Each 2'-hydroxyl Into Effects Onmentioning
confidence: 99%
“…Early studies analyzed short DNA molecules containing a single ribonucleotide by X-ray diffraction (Ban et al, 1994;Egli et al, 1993;Wahl & Sundaralingam, 2000) or nuclear magnetic resonance (NMR) (Jaishree et al, 1993;Chou et al, 1991) and consistently report that the B-form conformation usually adopted by DNA shifts either partially (i.e., locally) or completely to the A-form typical of RNA molecules. Early studies analyzed short DNA molecules containing a single ribonucleotide by X-ray diffraction (Ban et al, 1994;Egli et al, 1993;Wahl & Sundaralingam, 2000) or nuclear magnetic resonance (NMR) (Jaishree et al, 1993;Chou et al, 1991) and consistently report that the B-form conformation usually adopted by DNA shifts either partially (i.e., locally) or completely to the A-form typical of RNA molecules.…”
Section: Unrepaired Rnmps Affect Dna Structurementioning
confidence: 99%